2002
DOI: 10.1128/jvi.76.10.5082-5093.2002
|View full text |Cite
|
Sign up to set email alerts
|

Cytopathic Killing of Peripheral Blood CD4+T Lymphocytes by Human Immunodeficiency Virus Type 1 Appears Necrotic rather than Apoptotic and Does Not Requireenv

Abstract: An important unresolved issue of AIDS pathogenesis is the mechanism of human immunodeficiency virus (HIV)-induced CD4(+) T-lymphocyte destruction. We show here that HIV type 1 (HIV-1) exerts a profound cytopathic effect upon peripheral blood CD4(+) T lymphocytes that resembles necrosis rather than apoptosis. Necrotic cytopathology was found with both laboratory-adapted strains and primary isolates of HIV-1. We carefully investigated the role of env, which has been previously implicated in HIV cytopathicity. HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0
6

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 91 publications
3
58
0
6
Order By: Relevance
“…Controversy still exists not only about the mechanism of cell death but also about the occurrence of apoptosis in infected or uninfected bystander cells. [1][2][3][4][5] In the present work, we clearly demonstrate using the green fluorescence-based reporter system that HIV-1 induces apoptosis in CEM-GFP cells and it definitively occurs in both infected and uninfected bystander cells. In the present study, we have used a novel strategy to isolate apoptotic and nonapoptotic cells from the mixed population of HIV-1-infected cells using magnetic beads coated with Annexin.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Controversy still exists not only about the mechanism of cell death but also about the occurrence of apoptosis in infected or uninfected bystander cells. [1][2][3][4][5] In the present work, we clearly demonstrate using the green fluorescence-based reporter system that HIV-1 induces apoptosis in CEM-GFP cells and it definitively occurs in both infected and uninfected bystander cells. In the present study, we have used a novel strategy to isolate apoptotic and nonapoptotic cells from the mixed population of HIV-1-infected cells using magnetic beads coated with Annexin.…”
Section: Discussionmentioning
confidence: 79%
“…Several mechanisms have been proposed to account for the functional and quantitative loss of T cells, which include apoptosis, direct lysis by virus infection, necrosis, syncytium formation, anergy caused due to inappropriate signaling, autoimmunity, virusspecific immune response, super antigen-mediated deletion, upregulation of FasL-and activation-induced cell death. [1][2][3][4][5] Despite evidences for all these pathways by which HIV can induce cell death, apoptosis has been the major focus of research implicated in HIV-induced T-cell loss. [6][7][8] Various viral proteins such as Tat, Nef, Vpr, protease, and gp120 have also been individually implicated in initiation and/or intensification of the death process by regulating the apoptotic pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it was recently reported that the direct cytopathic effect of HIV1 in cycling, productively infected primary CD4 þ T cells does not require HIV Env interactions with its cellsurface receptors nor the presence of the Nef protein. 60 Whether the HIV1 factors required for the direct cytopathic effect of HIV1 in productively infected CD4 þ T cells 60 and for the indirect, bystander CD4 þ T-cell killing process that we identified here are, or not, the same is an important question that remains to be addressed.…”
Section: Discussionmentioning
confidence: 91%
“…The loss of cell resources and possible cytotoxic effects of viral proteins are likely to lead to an increase in the cell's death rate (Schneider and Shenk, 1987;Lenardo et al, 2002;Gustin and Sarnow, 2001). Further, assuming that the virion production rate is positively correlated with the density of viral peptides within the cytosol, one would expect the number of cell surface MHC-I molecules presenting viral peptides to increase with viral production rate, leading to an increase in the infected cell's death rate via cytotoxic T cell activity.…”
Section: Production-dependent Mortalitymentioning
confidence: 99%